PENGARUH KINERJA KOMPONEN ENVIRONMENTAL, SOCIAL, DAN GOVERNANCE TERHADAP KINERJA KEUANGAN (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia pada Periode 2016 - 2019) - Risky Rahmat Fadhillah; Marsono Marsono (Diponegoro Journal of Accounting, 2023)
This study aims to examine the relationship between the performance of environmental, social, and governance components on the financial performance of companies in Indonesia. This study uses financial performance represented by ROA as dependent variables and the performance of environmental, social, and governance components as independent variables. The population used in this study are companies listed on the Indonesia Stock Exchange (IDX) in 2016-2019. By using purposive sampling method, 332 samples were obtained for 4 consecutive years. This study uses panel data regression analysis with E-Views 12 to test the hypotheses . The findings of this study show that environmental performance has a significant negative effect on ROA, social performance has a positive insignificant effect on ROA, and governance performance has a significant negative effect on ROA. These results show that there are differences in results from most previous studies and stakeholder theory, so it is hoped that future researchers can further analyze the causes of these results.